Intercultural Relations and Stereotypes among Afghan Immigrants in Iran: A Qualitative Study - Zandi-Navgran, Leila; Berry, John W; Afrasiabi, Hossein (Journal of Ethnic and Cultural Studies, 2026)
For over four decades, Iran has become increasingly culturally diverse due to the influx of Afghan immigrants. This study explores the dynamics of stereotypes and intercultural relations experienced by Afghan immigrants in Iran. Adopting a constructivist perspective, it seeks to understand the forms of stereotyping and intercultural encounters and the meanings participants attribute to them. Data were collected and analyzed using Constructivist Grounded Theory, which involved initial, focused, and theoretical coding. The analysis revealed eleven core categories: self-superiority attitude, Afghan label, negative perceptions of being Afghan, judging by appearances, feelings of humiliation, striving for acceptance, resilience, identity assimilation, language and accent adaptation, and sedentary orientation. The findings indicate that immigrants encounter three interrelated phenomena in their intercultural relations with natives: negative stereotypes (cognition), negative attitudes (evaluation), and a sense of discrimination (behavior). In response to these challenges, Afghan immigrants engage in strategies such as striving for acceptance, resilience, identity negotiation, language and accent adaptation, and settling into sedentary practices. The study concludes that the intercultural adaptation of Afghan immigrants in Iran remains limited, constrained by structural and social barriers.